A Transcriptional Signature of PDGF-DD Activated Natural Killer Cells Predicts More Favorable Prognosis in Low-Grade Glioma - Sun, Yuhan; Sedgwick, Alexander James; Palarasah, Yaseelan; Mangiola, Stefano; Barrow, Alexander David (Frontiers in Immunology, 2021)
The binding of platelet-derived growth factor D (PDGF-DD) to the NKp44 receptor activates a distinct transcriptional program in primary IL-2 expanded human natural killer (NK) cells. We were interested in knowing if the PDGF-DD-NKp44 pathway of NK cell activation might play a clinically relevant role in anti-tumor immunity. In order to address this question, we generated transcriptional signatures unique to resting, IL-2 expanded, and PDGF-DD activated, NK cells, in addition to different T cell subsets, and established the abundance of these immune cell phenotypes in The Cancer Genome Atlas low-grade glioma (LGG) dataset using CIBERSORT. Our results show that a high abundance of the PDGF-DD activated NK cell or memory CD8+ T cell phenotypes are associated with a more favorable LGG prognosis. Combined cell phenotype analyses revealed that high abundance of the PDGF-DD activated NK cell phenotype with the CD4+ T helper cell phenotype in LGG tumors is also associated with more favorable prognosis. Finally, expression of transcripts encoding members of the killer cell lectin-like receptor (KLR) family, such as KLRK1 and KLRC2, KLRC3 and KLRC4 are associated with more favorable LGG prognosis, suggesting that these NK cell family receptors may play a prominent role in LGG anti-tumor immunity. Our results provide transcriptomic evidence that PDGF-DD activated NK cells play an important clinical role in immune surveillance of LGG.